The Influence of Think Pair Share Model Assisted by Mind Mapping Media at Fourth Grade Science Competence - Wisnuardani, Anak Agung; Surya Abadi, Ida Bagus Gede (Journal of Education Technology, 2020)
The application of the think pair share model is carried out to increase the enthusiasm for learning science with the help of Mind Mapping in grade IV SD students. This study aims to determine the effect of think pair share with the mind mapping media for science knowledge competency of the fourth grade students at elementary school. This type of quasi-experimental research (quasi-experimental) used the Nonequivalent Control Group Design. The population in school lessons is 153 students,  all grade IV SD. Sampling using random sampling technique,  randomizing the class. The selected sample was SD with 31 students as the experimental class and SD with 30 students as the control class. Science knowledge competency data were collected using objective tests. Data analysis using t-test. The results of the t-test analysis obtained tcount = 7.104> ttable = 2,000, at a significance level of 5% with dk = 59.It means that there is a significant difference in the competence of science knowledge between students who are taught using think pair share models assisted by mind mapping media and students being taught using conventional class IV SD learning. The average score of knowledge competency in the science experimental group x ̄ = 83.30> x ̄ = 67.96 the mean scoree of the control group. Thus it can be ignored that there is an influence of the think pair share model assisted by mind mapping media on the competence of science knowledge in grade IV SD.